Human Resources Development Strategy In Baitul Mal Watamwil An-Najah, Pekalongan District - Hartono, Bambang Sri; Rohmah, Farida; Budiharjo, Arif (Department of Islamic Banking, Faculty of Islamic Economics and Business, Institut Agama Islam Negeri Pekalongan, 2021)
This study aims to describe the strategy of human resource development, to analyze the internal and external environment of the business, and to develop a development plan on human resource aspect in Baitil Mal Wa Tamwil An-Najah. This study is a field research and the approach used in this study is qualitative method. It was done at Baitul Mal wa Tamwil An-Najah Pekalongan Regency since July until December 2017. Data collection technique in this study is through observation, interview, and documentation. This study uses descriptive analysis technique that aims to provide description about research subject based on data and variable obtained. There is also SWOT analysis to provide some recommendations for the company in its employees’ development in order to achieve company goal. Based on this study revealed that the human resource development strategy in Baitul Mal wa Tamwi An-Najah Pekalongan Regency is through orientation program, training and education, and career development. Through the SWOT analysis it is obtained points of development plans related to human resource aspect in Baitul Mal wa Tamwil An-Najah that can be a recommendation and reminder for the company. The development plans are built by SO strategy (Strength-Opportunity), WO strategy (Weakness-Opportunity), ST strategy (Strength-Threats), and WT strategy (Weakness-Threats) that the company has. By the analysis hopefully it can improve the strategy on human resource development.